2021
DOI: 10.1155/2021/6629105
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Dynamic Model of Resource Diffusion and Epidemic Spreading in Time‐Varying Multiplex Networks

Abstract: In the real world, individual resources are crucial for patients when epidemics outbreak. Thus, the coupled dynamics of resource diffusion and epidemic spreading have been widely investigated when the recovery of diseases significantly depends on the resources from neighbors in static social networks. However, the social relationships of individuals are time-varying, which affects such coupled dynamics. For that, we propose a coupled resource-epidemic (RNR-SIS) dynamic model (coupled model for short) on a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…In recent years, an increasing focus within disciplines such as statistical physics and computer science has been directed toward the examination of evolving network models [24]. Addressing this context, Huang et al formulated a coupled resource-epidemic dynamic model on the temporal network and analyzed the asymmetric interactions between the epidemic and the resource [25]. Guo et al further enriched the understanding of temporal networks by introducing a two-layer network framework with partial mappings [26].…”
Section: Open Accessmentioning
confidence: 99%
“…In recent years, an increasing focus within disciplines such as statistical physics and computer science has been directed toward the examination of evolving network models [24]. Addressing this context, Huang et al formulated a coupled resource-epidemic dynamic model on the temporal network and analyzed the asymmetric interactions between the epidemic and the resource [25]. Guo et al further enriched the understanding of temporal networks by introducing a two-layer network framework with partial mappings [26].…”
Section: Open Accessmentioning
confidence: 99%
“…Based on the assumption of constant thresholds, because of variations in the average degree, saddle-node bifurcation occurs, leading to a continuous increase and subsequent discontinuous decrease in the final adoption size with increasing network average degree. Research has found that factors such as the initial number of seeds [16,17], clustering coefficient [18], multilayer networks [19], network temporal dynamics [20] and timevarying [21] significantly affect information propagation in the threshold model.…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of researchers have employed a dual-layer network structure, to establish coupled information–epidemic propagation models, aiming to expound upon the reciprocal relationship between the spread of epidemic-related information and the proliferation of the epidemic itself [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Within this framework, the lower-layer network represents the epidemic spreading stratum, with nodes symbolizing individuals, and edges signifying physical contact relationships in reality.…”
Section: Introductionmentioning
confidence: 99%